Exercises in the Transcription of Contemporary Italian Architecture. The competition project for the New Passenger Terminal at Termini Rail Station (1947-'48) (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
The essay documents a lengthy research by Lucio Valerio Barbera on the well-knowncompetition project for the New Passenger Terminal at Termini Rail Station (1947-'48) by Ludovico Quaroni, Mario Ridolfi, Aldo Cardelli, Mario Fiorentino, Giulio Ceradini, Aldo Carè. This articulated and complex study – presented here in its definitive version as an exercise of "transcription" – examines a project that belongs to the intriguing events of modern architecture in Rome in the wake of the Second World War.